Preschool children’s attitudes towards their peers with special needs - Reis, Helena (2022)
This study explores children’s attitudes towards their peers with special needs (SN) at a preschool level. A total of 151 children were examined using the Acceptance Scale for Kindergarteners – Revised and social demographic questionnaires to collect information from parents and educators. The research included preschool children (5 years old) attending private preschools in a city of Portugal- Leiria-as well as their corresponding parents and educators. Further, 10 classrooms within preschools participated in the study, with a sample of 151 children, 149 parents, and 14 educators. Internal consistency was calculated, and the Cronbach’s α coefficient for the complete scale was .688. Results revealed that the average score associated with children’s attitudes was 18.78 (DP = 5.88). Children have more positive attitudes if they are in contact with peers with special needs regardless of the location (p < .05). Although children who have contact with peers with special needs in classroom have positive attitudes (p < .01) those who have contact in the preschool (outside classroom) have much more (p < .01). The results of this study provide insights into children’s attitudes and reveal that closer contact with children with special needs benefits peer attitudes.